Are Psychologic Factors Associated With Shoulder Scores After Rotator Cuff Surgery?. Issue 10 (October 2018) - Thorpe, Alison M.; O'Sullivan, Peter B.; Mitchell, Tim; Hurworth, Mark; Spencer, Jonathan; Booth, Grant; Goebel, Sven; Khoo, Paul; Tay, Aaron; Smith, Anne
Abstract: Background: Psychologic factors are associated with pain and disability in patients with chronic shoulder pain. Recent research regarding the association of affective psychologic factors (emotions) with patients' pain and disability outcome after surgery disagrees; and the relationship between cognitive psychologic factors (thoughts and beliefs) and outcome after surgery is unknown. Questions/purposes: (1) Are there identifiable clusters (based on psychologic functioning measures) in patients undergoing shoulder surgery? (2) Is poorer psychologic functioning associated with worse outcome (American Shoulder and Elbow Surgeons [ASES] score) after shoulder surgery? Methods: This prospective cohort study investigated patients undergoing shoulder surgery for rotator cuff-related shoulder pain or rotator cuff tear by one of six surgeons between January 2014 and July 2015. Inclusion criteria were patients undergoing surgery for rotator cuff repair with or without subacromial decompression and arthroscopic subacromial decompression only. Of 153 patients who were recruited and consented to participate in the study, 16 withdrew before data collection, leaving 137 who underwent surgery and were included in analyses. Of these, 124 (46 of 124 [37%] female; median age, 54 years [range, 21-79 years]) had a complete set of four psychologic measures before surgery: Depression, Anxiety and Stress Scale; Pain Catastrophizing Scale; Pain Self-Efficacy Questionnaire; and Tampa Scale for Kinesiophobia. The existence of clusters of people with different profiles of affective and cognitive factors was investigated using latent class analysis, which grouped people according to their pattern of scores on the four psychologic measures. Resultant clusters were profiled on potential confounding variables. The ASES score was measured before surgery and 3 and 12 months after surgery. Linear mixed models assessed the association between psychologic cluster membership before surgery and trajectories of ASES score over time adjusting for potential confounding variables. Results: Two clusters were identified: one cluster (84 of 124 [68%]) had lower scores indicating better psychologic functioning and a second cluster (40 of 124 [32%]) had higher scores indicating poorer psychologic functioning. Accounting for all variables, the cluster with poorer psychologic functioning was found to be independently associated with worse ASES score at all time points (regression coefficient for ASES: before surgery -9 [95% confidence interval CI, -16 to -2], p = 0.011); 3 months after surgery -15 [95% CI, -23 to -8], p < 0.001); and 12 months after surgery -9 [95% CI, -17 to -1], p = 0.023). However, both clusters showed improvement in ASES score from before to 12 months after surgery, and there was no difference in the amount of improvement between clusters (regression coefficient for ASES: cluster with poorer psychologic function 31 [95% CI, 26-36], p < 0.001); cluster with better psychologic function 31 [95% CI, 23-39], p < 0.001). Conclusions: Patients who scored poorly on a range of psychologic measures before shoulder surgery displayed worse ASES scores at 3 and 12 months after surgery. Screening of psychologic factors before surgery is recommended to identify patients with poor psychologic function. Such patients may warrant additional behavioral or psychologic management before proceeding to surgery. However, further research is needed to determine the optimal management for patients with poorer psychologic function to improve pain and disability levels before and after surgery. Level of Evidence: Level II, therapeutic study.